2014
DOI: 10.1007/s11999-014-3660-4
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Use After Fracture Surgery Correlates With Pain Intensity and Satisfaction With Pain Relief

Abstract: Background In 2012, Medicare began to tie reimbursements to inpatient complications, unplanned readmissions, and patient satisfaction, including satisfaction with pain management. Questions/purposes We aimed to identify factors that correlate with (1) pain intensity during a 24-hour period after surgery; (2) less than complete satisfaction with pain control; (3) less than complete satisfaction with staff attention to pain relief while in the hospital; and we also wished (4) to compare inpatient and discharge s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
98
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 159 publications
(103 citation statements)
references
References 34 publications
5
98
0
Order By: Relevance
“…The evidence that psychological factors (depression, pain anxiety, and greater catastrophic thinking) are strongly associated with pain intensity after musculoskeletal trauma is compelling [6,24,27]. These aspects of the human illness experience are amendable to cognitive behavioral therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence that psychological factors (depression, pain anxiety, and greater catastrophic thinking) are strongly associated with pain intensity after musculoskeletal trauma is compelling [6,24,27]. These aspects of the human illness experience are amendable to cognitive behavioral therapy.…”
Section: Discussionmentioning
confidence: 99%
“…One might expect patients with injuries to larger bones, certain anatomic areas, more than one fracture, or specific procedures to have greater pain and use more opioids, but that was not the case [4,6]. Previous research also found an association between greater This work was performed at the Massachusetts General Hospital -Harvard Medical School.…”
Section: Introductionmentioning
confidence: 99%
“…Despite uncertainty regarding the long-term effectiveness of opioids for treating chronic musculoskeletal pain [35,43] and emerging evidence that preoperative opioid use is associated with greater pain, disability, and dissatisfaction after orthopaedic surgery [10,25,31,32,42,53], opioids continue to be prescribed. Although it is well established that high-risk opioid use (abuse or dependence) may result from prolonged opioid exposure during the preoperative period [57], little is known about its prevalence and effect in the perioperative orthopaedic surgery setting.…”
Section: Introductionmentioning
confidence: 99%
“…The higher morphine equivalence dose administered to patients whose pain worsened in this study resembles that of studies of postoperative pain where higher opioid use has been associated with greater pain intensity (Bot, Bekkers, Arnstein, Smith, & Ring, 2014). Higher analgesic use has also been found following surgery in patients who are younger, have emergency surgery, experience pre-operative pain and high anxiety (Ip, Abrishami, Peng, Wong, & Chung, 2009).…”
Section: Discussionmentioning
confidence: 75%